Environmental Education Based on Women's Empowerment to Support Sustainable Environmental Management in Kabupaten Pangkajene dan Kepulauan - Abdul Muin; Rahma Amin; Dety Yunita Sulanjari (Jurnal Pedagogi dan Inovasi Pendidikan, 2026)
Limited environmental literacy and the underrepresentation of women in environmental management remain significant challenges to achieving sustainable development in Pangkajene and Kepulauan Regency, Indonesia. These conditions highlight the need for environmental education programs that not only improve community knowledge but also strengthen women's capacity as key agents of environmental stewardship. This Community Service Program aimed to enhance community environmental literacy through women's empowerment-based environmental education to support sustainable environmental management. The program was implemented in Balocci Baru Village using participatory and collaborative approaches involving community leaders, women's groups, youth organizations, and local government officials. The activities included environmental assessments, environmental education sessions, waste management training, participatory discussions on gender equality, community clean-up campaigns, and collaborative planning for the establishment of a community environmental group and a community-based waste bank. The program resulted in an increase in participants' understanding of environmental management from 50% to 80%, greater awareness of women's strategic role in environmental conservation, and a stronger community commitment to establishing inclusive environmental initiatives. These findings demonstrate that women's empowerment-based environmental education is an effective approach to improving environmental literacy, strengthening community participation, and promoting sustainable environmental management at the community level.